«No lo había visto de ese modo»: Contexto y Enmarcación en Persuasión - Lleón , José Lluis (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2007)
The paradigms of research and practice of public persuasion are suddlenly changing. We are overcoming the concepts of saying/visualizing, to get to the frames to use so that saying is acceptable. The persuasion by framing was initially developed from the studies concerning evaluation of the utility of decisions. In this article, we show the derivations of the framing theories applied to advertising, the framing models and especially a positive-negative frame type. Although framing has always been used in advertising persuasion, there is no theory developed to guide, in a conscious and systematic way, the elaboration of contexts of persuasive condicitiong in commercial messages. This article contributes to de development of a coming theory for advertising framing.